2012
DOI: 10.1159/000339261
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Nonfat Milk Results in a Less Atherogenic Lipoprotein Profile: A Pilot Study

Abstract: Background: An increase in plasma low-density lipoprotein (LDL) is a well-known risk factor in the development of atherosclerosis. Dairy consumption may lower the risk of atherosclerosis; however, studies on the effects of milk on cardiovascular risk factors are still scarce. We were interested in investigating whether the intake of milk improves the atherogenic lipoprotein profile. Aims: We investigated the effects of consuming whole or nonfat milk on plasma lipoprotein composition in healthy Japanese subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Similar conclusions were drawn from a small crossover RCT comprising 8 healthy men in whom consumption of whole-fat milk or skimmed milk for 6 wk had no impact on fasting TG concentrations (23). On the other hand, consumption of skimmed milk (500 mL/d) for 2 wk was shown to reduce fasting TG concentrations compared with whole-milk consumption in 14 normolipidemic subjects (34). …”
Section: Dairy and Cardiometabolic Disease Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions were drawn from a small crossover RCT comprising 8 healthy men in whom consumption of whole-fat milk or skimmed milk for 6 wk had no impact on fasting TG concentrations (23). On the other hand, consumption of skimmed milk (500 mL/d) for 2 wk was shown to reduce fasting TG concentrations compared with whole-milk consumption in 14 normolipidemic subjects (34). …”
Section: Dairy and Cardiometabolic Disease Risk Factorsmentioning
confidence: 99%
“…Consuming nonfat milk (500 mL/d) for 2 wk was shown to increase LDL size in a small group of 14 healthy normolipidemic Japanese subjects (34). …”
Section: Dairy and Cardiometabolic Disease Risk Factorsmentioning
confidence: 99%
“…7, 9, 10, 11, 12, 13, 14 These include: an association with reduced body mass index (BMI) and waist circumference; 10 improvement of blood lipid profiles; 11, 12, 13 reduced risk of hypertension; 14 improvement of glycaemic responses 15 and reduced risk of type 2 diabetes. 16, 17 However, conflictions exist in the current literature, with a number of reports observing no association with dairy intake and various markers of metabolic health.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of cohort studies have also shown that milk intake was associated with a reduced risk of hypertension [ 14 , 15 ], but not with type 2 diabetes risk [ 16 – 18 ]. On the other hand, data from randomized clinical trials having assessed the impact of milk consumption on cardiometabolic risk factors are mixed and not fully consistent with data from epidemiological studies [ 19 – 24 ].…”
Section: Introductionmentioning
confidence: 99%